Interaction of serine/threonine protein phosphatase 5 with the protein products of tumour suppressor gene Tsc2 - Malanchuk, O.M.; Palchevskyy, S.S.; Pozur, V.K.; Gout, I.T.; Filonenko, V.V. (Біополімери і клітина, 2007)
Tuberous sclerosis (TSC) is a tumour disease caused by mutations in Tsc1 or Tsc2 genes. Both protein products of Tsc1 and Tsc2 form an intracellular complex possessing GTPase-activating (GAP) activity towards a small GTP binding protein Rheb. The activity of TSC1/2 complex is regulated by multiple phosphorylations of TSC2 mediated by several kinases, such as PKB/Akt, AMP-activated kinase (AMPK), ERK, MK2 and RSK1. So far, very little is known about the molecular mechanisms of TSC2 dephosphorylation. In the yeast two-hybrid screening, we have identified a number of potential TSC2 binding partners including protein phosphatase 5 (PP5). In this study, we provide the evidence that the interaction between TSC2 and PP5 also occurs in mammalian cells. Using TSC2 ⁺/⁺, p53 ⁻/⁻ mouse embryo fibroblasts (MEFs) transiently overexpressing myc-PP5, we showed in the immunoprecipitation assay that TSC2 specifically associates with myc-PP5 in exponentially growing cells. The physiological relevance of identified interaction, especially the involvement of PP5 in the dephosphorylation of major regulatory sites is currently under investigation.